Identifikasi Kearifan Lokal dalam Pemanfaatan Jenis-Jenis Tumbuhan Untuk Ketahanan Pangan Dan Obat-Obatan - Anggraini, Yustina; Matius, Paulus; Hastaniah, Hastaniah; Diana, Rita (Universitas Pattimura, 2020)
This research aims to inventory local wisdom in the management and utilization of plants as food and medicine by local communities. The method conducted in this study is the purposive sampling method that aims to inventory plant species, direct observation, and analyze data by calculating density and basal area. The results showed 243 individual plants, consisting of 53 types of trees from 17 families, and found 29 types of plants were used as food and medicine. The utilization of plants by local communities varies. People use plant species for various benefits, namely foodstuffs, building materials, handicrafts, and traditional medicines. Local wisdom in the local community is the knowledge that lasts for generations and has a symbiotic relationship of mutualism with the forest ecosystem at the research site.